REINTERPRETASI KISAH NABI AYYUB UNTUK KONSEP SELF-CONTROL: ANALISIS TEORI DOUBLE MOVEMENT - Alhusaini, Zikron Fadhil; Muallim, Mohammad; Ghifari, Muhammad (Al - Tadabbur: Jurnal Ilmu Al-Qur'an dan Tafsir, 2025)
Every human being faces life's trials, such as physical suffering, loss, and psychological stress, which often lead to emotional instability and a negative impact on quality of life. Self-Control is very important, especially in the context of stressful modern life. However, in Indonesia, there are still many individuals who do not understand this concept properly, leading to high rates of mental disorders, depression, and destructive actions. One of the figures in Islam who represents Self-Control is Prophet Ayyub a.s., who is known for his patience in the face of severe suffering. His story is recorded in QS. Al-Anbiya (21:83-84) is generally understood in terms of patience alone, but has not been studied much from a psychological perspective as a form of Self-Control. Therefore, this study aims to reinterpret the story of Prophet Ayyub a.s. to examine the values of Self-Control in it through Fazlur Rahman's double movement hermeneutic approach, in order to understand the historical context and its actualization in the present. This research is qualitative with a double movement hermeneutic approach through two movements of interpretation: from the past context to universal moral principles, then re-contextualized in the present situation. The results show that the story of Prophet Ayyub a.s. not only shows patience, but a form of Self-Control that is active, spiritual, and solutive. In conclusion, the story of Prophet Ayyub can be reflected upon as a relevant model of Self-Control to strengthen mental health in contemporary society.